Effect of age on carcass weight, carcass yield and muscle mass in growing and fattening guinea pigs (Cavia porcellus) - Felipe Escobar-Ramírez; Jaime Antonio Ruíz-Béjar; Rene Antonio Hinojosa-Benavides; Ruggerths Nilo De la Cruz-Marcos; David Ruíz-Vílchez (Journal of the Selva Andina Animal Science)
The aim of the study was to determine the influence of age on the level of dry matter intake (DMI) and weight gain (WG) per unit weight, carcass weight and yield (WS and YC) and muscle mass (PMM, RMM) in guinea pigs. We worked with 80 guinea pigs that were slaughtered at 63, 77, 91 and 105 days of age (treatments 1 to 4, respectively), starting with male gazapos weaned at 21±3 days of age, with an average weight of 345 g and continued until the ages indicated in each treatment, determining the level of CMS, WG, YC and RMM. The determination of YC and MMR was carried out by obtaining the carcasses of 4 animals from each treatment. When statistically analyzed, it was determined that both CMS and WG per unit weight were inversely correlated with the age of the animal. During the first 14 days of feeding, the guinea pigs daily grew 4.20 % of live weight (BW), a level that gradually and significantly decreased to 1.55 % in the last 14 days, with daily increases of 14.5-12.1 g, reaching the ideal marketing weight (920-950 g) at 77 days of age. For WG (903.6, 1127.3, 1303.4 and 1353.9 g), statistical differences were obtained (p˂ 0.01), except similarity in gain achieved at 91 and 105 days of age. The feed conversion ratio (FCR), decreases with the age of the animals, from 3.47 g of DM needed per kg of WG in the first stages, increases to 6.16 kg for the same increase in the last period evaluated, determining that this character has an inverse correlation with age. WC and WMP tend to increase as a function of the age of the animals and in accordance with the increase in BW, however, the significant changes (p˂ 0.01), occur up to 91 and 77 days of age, respectively. Finally, on the YC (free head, limbs and red viscera (53.7, 54.1, 53.3 and 53.1%) and the MMR, no effect of the age of the guinea pig in the rearing stage has been determined.